New Hart's rules : the Oxford style guide - Waddingham, Anne. (United Kingdom : Oxford University Press, 2014)
Hart's Rules has been the authority on style, helping writers and editors prepare copy for publication. The latest edition of this guide has been updated for the twenty-first century using the resources of Oxford Dictionaries and with the advice of publishing experts. Twenty-one chapters give information on all aspects of writing and of preparing copy for publication.
Chapter 1: The parts of a book -- Chapter 2:Preparing copy -- Chapter 3:Spelling and hyphenation -- Chapter 4:Punctuation -- Chapter 5:Capitalization -- Chapter6. Names -- Chapter7. Italic, roman, and other type of treatment -- Chapter8. Work titles in text -- Chapter9. Quotations and direct speech -- Chapter10. Abbreviations and symbols -- Chapter11. Numbers and dates -- Chapter12. Languages -- Chapter13. Law and legal references -- Chapter14. Science, math and computing -- Chapter15. Lists and tables -- Chapter16. Illustrations and artworks -- Chapter17. Notes and references -- Chapter18. Bibliography -- Chapter19. Indexing -- Chapter20. Copyright and other publishing responsibilities -- Chapter21. US and British English .
Includes index.
Keywords: LANGUAGE ARTS & DISCIPLINES